Pengaruh Lingkungan Kerja dan Komunikasi Interpersonal terhadap Semangat Kerja Pegawai Pada SPBE PT Elnusa Petrofin Bima - Indra Jaya; Jaenab; Muhammad Badar (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
This study aims to analyze the effect of work environment and interpersonal communication on employee morale at SPBE PT Elnusa Petrofin Bima. The research method used is a quantitative approach with a causal associative design. The population consists of all 39 employees of SPBE PT Elnusa Petrofin Bima, and the entire population was taken as the sample using a saturated sampling technique. Data were collected through observation, literature study, and questionnaires. The data were analyzed using validity and reliability tests, classical assumption tests, multiple linear regression, t-test, and f-test. The results show that: (1) the work environment does not have a significant effect on employee morale; (2) interpersonal communication has a significant effect on employee morale; and (3) work environment and interpersonal communication simultaneously have a significant effect on employee morale. Thus, interpersonal communication is the dominant factor in improving employee morale at SPBE PT Elnusa Petrofin Bima.